Santuario del Padre Hurtado - Undurraga & Devés Arquitectos (1998)
Detalles y propósitos del proyecto
Keywords: CHILE; INTERVENCIONES URBANAS; SANTUARIOS; MONUMENTOS FUNERARIOS; UNDURRAGA, CRISTIAN; DEVÉS, ANA LUISA; ARQUITECTURA RELIGIOSA